A Review on Antidiabetic Properties of Indian Mangrove Plants with Reference to Island Ecosystem. (5th December 2019) - Sachithanandam, V.; Lalitha, P.; Parthiban, A.; Mageswaran, T.; Manmadhan, K.; Sridhar, R.
Abstract : Mangrove ecosystem has many potential species that are traditionally used by the coastal communities for their traditional cure for health ailments as evidenced by their extensive uses to treat hepatic disorders, diabetes, gastrointestinal disorders, anti-inflammation, anticancer, and skin diseases, etc. In recent times, the diabetes mellitus (DM), a serious physiological disorder all over the world, occur due to the relative or complete deficiency of insulin in the body, characterized by an abnormally high blood glucose level. India has a rich traditional knowledge on plant-based drug formulations that are protective and curative for many health ailments. In this context, we aimed to compile the works done on the antidiabetic activities of mangrove species from Indian coastal regions especially on Andaman and Nicobar Islands as well as some recent works reported from other countries. A total of 126 published articles and 31 mangrove species related pieces of information were gathered with reference to antidiabetic properties of mangroves. This review summarizes the chemical structures, molecular formula, molecular weight, and their biological activities with an aspiration that it might be helpful for the future bioprospecting industries who are interested in develop the natural drugs for DM.